Listening to the voices of Latina women: Sexual and reproductive health intervention needs and priorities in a new settlement state in the United States. Issue 9 (1st September 2016) - Mann, Lilli; Tanner, Amanda E.; Sun, Christina J.; Erausquin, Jennifer Toller; Simán, Florence M.; Downs, Mario; Rhodes, Scott D.
ABSTRACT: Latina women in the United States are disproportionately affected by negative sexual and reproductive health outcomes. Our community-based participatory research partnership conducted in-depth interviews exploring sexual and reproductive health needs and priorities with 25 Latinas in North Carolina and identified themes through constant comparison, a grounded theory development approach. Participants described individual-, interpersonal-, and clinic-level factors affecting their sexual and reproductive health as well as potentially successful intervention characteristics. Our findings can be used to inform culturally congruent interventions to reduce sexual and reproductive health disparities among Latinas, particularly in new settlement states in the southeastern United States.